Consolidation of the Gaia catalogue with Chinese Space Station Telescope astrometry - Gai, M.; Vecchiato, A.; Busonero, D.; Riva, A.; Cancelliere, R.; Lattanzi, M.; Qi, Z. (Frontiers in Astronomy and Space Sciences, 2022)
The issue of preservation and improvement of the Gaia catalogue throughout the next few decades is addressed. The goal of this paper is to evaluate the feasibility of astrometric parameter update, for objects already in the catalogue, by inclusion of new observations from other space missions, in particular CSST. The proposed approach consists in modelling the astrometric fit of sources in the extragalactic region of the Gaia sample with new observations, using the stars in the local field as reference for each target. The concept is verified by simulation, in the framework of the expectations on the Gaia astrometric performance and on the data from the forthcoming CSST Optical Survey. This approach can mitigate the natural degradation of the initial precision on coordinates of Gaia sources with time by improving proper motions by a factor > 3, thus improving the positional precision in future epochs. Moreover, the catalogue is densified by inclusion of objects below the Gaia limiting magnitude, improving on the Galactic population census, and on extragalactic population. CSST-OS data will reduce the Gaia precision degradation on positions by a factor 2.7 over 30 years, and increase the number of available reference sources over 40% of the sky. Future observations from other missions may further improve on the Gaia catalogue by extending the sky coverage and temporal baseline.